Resuscitation Fluid Requirements in Burn Injury Patients Using Intravenous Vitamin C: An Evidence Based Case Report - Hendra Hendra; Davie Muhamad; Diyah Eka Andayani (World Nutrition Journal, 2021)
Background: Based on the Guideline of European Society for Clinical Nutrition and Metabolism (ESPEN) in 2013, vitamin C is an additional therapy for burn patients during the resuscitation process and reduce the amount of fluid resuscitation but still needs further evidence. This study aims to find the effect of intravenous vitamin C administration to reduce the fluid requirements during first 24 hours resuscitation in burn patients.Methods: Electronic Literature search were performed in PubMed, Cochrane, Scopus and ProQuest databases. Hand searching was also performed. MesH Term was used in PubMed database searching. All literature obtained was screened based on inclusion and exclusion criteria.Results: Three articles were selected based on the eligibility criteria. Two Randomized Controlled Trial / RCT studies concluded that intravenous vitamin C administration reduced resuscitation fluid requirements in burn patients. But in the case control study there was no significant difference in resuscitation fluid requirements between the two groups. Other study reported that there were significant differences in resuscitation fluid requirements between the two groups. Both RCT studies did not use the blinding method and explained the side effects of therapy. A case control study reported an increase in cases of acute kidney failure in the vitamin C group compared to control (23% vs 7%) although it was not statistically significant.Conclusions: Intravenous vitamin C can reduce the resuscitation fluid requirements in the first 24 hours in burn patients (grade C recommendation).